An Exploratory Study of the Effects of Units Pricing and Nutritional Labelling Upon Supermarket Choice - Mathews, H. Lee (Institutional Knowledge at Singapore Management University, 1974)
Studies the effects of unit pricing and nutritional labeling upon supermarket choice. Review of unit pricing literature during the late 1960s and early 1970s; Consumer awareness and use of unit pricing; Effects of unit pricing on shopper behavior.